Isolated Abdominal Circumference < 5% or Estimated Fetal Weight 10 to 19% as Predictors of Small for Gestational Age Infants - Turitz, Amy L.; Quant, Hayley; Schwartz, Nadav; Elovitz, Michal; Bastek, Jamie A. (American Journal of Perinatology, 2014)
Objectives To determine whether (1) isolated fetal abdominal circumference < 5% (AC5) in absence of growth restriction (estimated fetal weight < 10% [EFW10]) or (2) borderline fetal growth 10 to 19% (EFW10–19) predicts subsequent fetal and/or neonatal growth restriction.Study Design The authors performed a retrospective cohort study (January 2008 to December 2011) of women with singleton pregnancies between 26 and 36 weeks who had ≥ 1 growth ultrasound. Univariable and multivariable analyses were performed to determine the association between isolated AC5 or EFW10–19 with both subsequent sonographic diagnosis of EFW10 and neonatal diagnosis of small for gestational age (SGA). Test characteristics were calculated.Results Out of the 10,642 pregnancies, prevalence of isolated AC5, EFW10–19, EFW10, and SGA were as follows: AC5, 5.31%; EFW10–19, 13.30%; EFW10, 7.95%; and SGA, 17.63%. While screening for SGA using EFW10 alone would miss 68.34% of SGA neonates, using isolated AC5 would identify an additional 16.15% of SGA neonates with a 3.7% false positive rate. Using EFW10–19 would identify an additional 40.20% of SGA neonates with a 9.0% false positive rate.Conclusion Fetuses with isolated AC5 or EFW10–19 are at an increased risk of growth restriction. Using isolated AC5 or composite EFW10–19 would identify SGA neonates that are missed using conventional sonographic definitions of growth restriction alone.
Keywords: abdominal circumference; estimated fetal weight; intrauterine growth restriction; small for gestational age; ultrasound